The Influence of Business Management and Micro-Credit Accessibility on MSME Performance and Its Impact on the Welfare of MSME Actors (Study on MSME Debtors of Bank Mandiri in Bandung City) - Abe Sanjaya; Asep Mulyana; Sutisna Sutisna (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Micro, Small and Medium Enterprises (MSMEs) are business sectors that have great potential to develop and contribute significantly to the national economy. However, MSMEs still face several obstacles in carrying out their business activities, namely weak management of Business Management and MSME accessibility to financing from financial service institutions. MSMEs can access operational funds and investment funds through microcredit. It is hoped that microcredit can help and encourage MSME actors to continue to develop and achieve optimal business performance and have a positive impact on the welfare of MSME actors. This study aims to analyze the Influence of Business Management and Microcredit Accessibility on MSME Performance and Its Impact on the Welfare of MSME Actors. This study was conducted on 240 MSME debtors of Bank Mandiri in Bandung City by distributing questionnaires. This study uses the Sequential Explanatory Analysis method using Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of this study indicate that effective Business Management and good Microcredit Accessibility have a positive and significant effect on improving MSME Performance and have a positive and significant impact on the Welfare of MSME Actors. This study is expected to provide comprehensive insights for MSME actors and stakeholders in formulating better MSME development strategies.